Perancangan Ulang Tata Letak Fasilitas Menggunakan Metode Systematic Layout Planning Pada PT Pilar Kekar Plasindo - Lulu Elvira; Bambang Suhardi; Rahmaniyah Dwi Astuti (Program Studi Teknik Industri Universitas Setia Budi, 2020)
Good equipment and product design are meaningless if there is no good layout planning. Problems that are owned by PT. Pilar Kekar Plasindo occurs in the production of small polyethylene. This is because small polyethylene production has large material total transfer distance. Small polyethylene problems, namely the distance between stations, cross-movement, backtracking, and the broken machine that is still placed in the production section. This makes the material handling costs and distances become large. So this research aims to produce a layout design of production facilities that can minimize the distance and cost of material movement. The method used is Systematic Layout Planning (SLP). Three alternative designs were compared, and the second proposed facility layout was chosen because it was able to reduce the total cost of material transfer by 68.3% and reduce the distance of material transfer by 59.6% from the initial facility layout.